The New Challenge in the Management of Proximal Femur Fractures during SARS Cov-2 outbreak - Matassi, Fabrizio; Piolanti, Nicola; Filoni, Gabriele; Giabbani, Niccolò; Nulvesu, Gianluca; Rostagno, Carlo; Civinini, Roberto; Scaglione, Michelangelo (Acta Biomedica Atenei Parmensis, 2021)
The aim of this study is to evaluate how the spread of Sars-Cov-2 has changed the epidemiology of proximal femur fractures in two major trauma centers in Italy, understanding the workload and the best allocation of the resources for the orthopedics department in such an emergency situation.The rate of patients from January 2019 to April 2020 hospitalized with femoral neck fractures (group A) and trochanteric fractures (group B) were recorded. Demographic data, timing of surgical treatment and the length of stay were recorded.Data show that the number of proximal femur fractures has remained unchanged in the COVID and pre-COVID era (ranging from an average of 91.14/month in the pre-COVID era to 76/month in March and 80/month in April). In our trauma centers, the rate of patients operated on within 48 hours has remained stable (78.19% vs 77.92%), while the length of stay has decreased during the COVID period (8.9 days vs 6.5 days in March and 6.8 days in April).Proximal femur fractures, even during the COVID period, are a constant issue and a new challenge for the healthcare system. The main goals of management are to preserve patients from viral infection, to provide early surgical treatment and fast track protocol for discharge.